COLABORAÇÃO E VANTAGEM COMPETITIVA NA CADEIA DE VALOR: UM ESTUDO NO SETOR DE AUTOPEÇAS - GONÇALVES, ALEXANDRE DOS SANTOS (2019)
The study of collaborative and competitive advantage in the value chain aims to describe and analyze ways and reasons regarding the relationship between the links, and how these processes may help them to generate value and competitiveness in their markets. Considering this competitive scenario, the search for companies for shorter terms and shorter costs, better quality and flexibility is a constant. In this way, auto parts companies have developed new configurations of value chain management for a new pattern of relationship with suppliers. From a qualitative and exploratory approach, we used the case study method to collect data. Thus, we interviewed a logistics professional from a large auto parts company, located in the city of São Paulo, seeking to verify the use of the value chain and collaborative practices in the company. As a result, the analysis showed that the company is still initiating a value chain process. We also found that possible changes in the business model through the reconfiguration and restructuring of its value chain, more specifically the extension of the chain partners, can offer a differential to this auto parts company and, consequently, for its customers.